1996
DOI: 10.1111/j.1574-6968.1996.tb08090.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of energy metabolism in the bradyzoites and tachyzoites ofToxoplasma gondii

Abstract: The bradyzoite and tachyzoite forms of Toxoplasma gondii, purified from infected animals, were analysed for their activities of phosphofructokinase, pyruvate kinase, lactate dehydrogenase, NAD(+)- and NADH-linked isocitrate dehydrogenases, and succinic dehydrogenase. Both developmental stages contained high activities of phosphofructokinase (specific for pyrophosphate rather than ATP), pyruvate kinase and lactate dehydrogenase, suggesting that energy metabolism in both forms may centre around a high glycolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…Another interesting group of chronic infection DEGs are those involved in glycolysis: glucose-6-phosphate isomerase, pyruvate kinase, lactate dehydrogenase 2, and glucosephosphate mutase. Previous data showed that tachyzoites and bradyzoites use the glycolytic pathway differently with lactate dehydrogenase 2 and pyruvate kinase being up-regulated during the bradyzoite stage [33, 34]. Our data shows that in addition to these two previously described bradyzoite-specific glycolytic enzymes, glucose-6-phosphate isomerase and glucosephosphate mutase are also more abundant in chronic vs acute infection.…”
Section: Resultssupporting
confidence: 60%
“…Another interesting group of chronic infection DEGs are those involved in glycolysis: glucose-6-phosphate isomerase, pyruvate kinase, lactate dehydrogenase 2, and glucosephosphate mutase. Previous data showed that tachyzoites and bradyzoites use the glycolytic pathway differently with lactate dehydrogenase 2 and pyruvate kinase being up-regulated during the bradyzoite stage [33, 34]. Our data shows that in addition to these two previously described bradyzoite-specific glycolytic enzymes, glucose-6-phosphate isomerase and glucosephosphate mutase are also more abundant in chronic vs acute infection.…”
Section: Resultssupporting
confidence: 60%
“…Glycolytic intermediates were generally more abundant in the infection metabolome, apart from 48 HPI when many were depleted. This result is expected given previous work demonstrating a highly active T. gondii glycolytic pathway and the energetic burden of infection on host cells [2,4,7,31]. Host hexose kinase (HK) and pyruvate kinase (PK) were transcriptionally upregulated in infected cells at every time point during infection (Table 1) and were highly transcribed throughout infection in T. gondii with FPKM values regularly at or above 50 (Table 2).…”
Section: Glycolysis Increasessupporting
confidence: 65%
“…Mature bradyzoites are adapted for lifelong persistence in their hosts and exhibit an extreme reduction in growth rate until complete cell cycle arrest (25), with the glycolytic pathway appearing as their main source of energy. In contrast, tachyzoites, which are present during the acute phase of disease, are characterized by a rapid doubling time of 6 to 8 h, indicating that this phase is an effective pathway for the acquisition of nutrients and energy metabolism (26) and for the use of the tricarboxylic acid cycle associated with the respiratory chain to obtain energy (27) (28).…”
Section: Discussionmentioning
confidence: 99%